Method for producing water dispersion, water dispersion, and aqueous ink

The method of producing raspberry-like titanium oxide composite particles in a water dispersion addresses the challenges of achieving high whiteness and stability in aqueous inks, resulting in improved ink performance.

JP2025040774APending Publication Date: 2025-03-25RISO KAGAKU CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023147789
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Existing methods for producing water dispersions for high whiteness aqueous inks face challenges in achieving stable dispersion, preventing pigment sedimentation, and maintaining high whiteness.

Method used

A method involving the production of a titanium oxide aqueous dispersion, followed by the addition of a polymerizable monomer and initiator to form raspberry-like titanium oxide composite particles, which are then used to create a water dispersion for high whiteness aqueous inks.

Benefits of technology

The method effectively produces a water dispersion that results in high whiteness aqueous inks with improved dispersion stability and redispersibility, while preventing pigment sedimentation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025040774000004
    Figure 2025040774000004
  • Figure 2025040774000005
    Figure 2025040774000005
  • Figure 2025040774000006
    Figure 2025040774000006
Patent Text Reader

Abstract

To provide a method for producing a water dispersion that can be used to obtain aqueous ink with high whiteness.SOLUTION: The method for producing a water dispersion includes a step 1 of obtaining a titanium oxide water dispersion containing titanium oxide particles, a dispersant, and water, and a step 2 of adding a polymerizable monomer and a polymerization initiator to the titanium oxide water dispersion to polymerize the polymerizable monomer and obtaining titanium oxide composite particles. The step 2 includes a step of adding the polymerizable monomer in a single addition at a weight ratio of 1 / 5 or more relative to the total amount of titanium oxide particles, and the polymerizable monomer includes polymerizable monomer A having a water solubility of 0.5 g / 100 ml or less at 23°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] An embodiment of the present invention relates to a method for producing an aqueous dispersion, the aqueous dispersion, and an aqueous ink. [Background technology]

[0002] 2. Description of the Related Art Methods for forming images such as letters, pictures, and designs on recording media such as film, cardboard, and cloth include screen printing and gravure printing, but in recent years, inkjet printing, which is essentially plateless, has been attracting attention.

[0003] When printing on a non-white recording medium, for example, a dark-colored recording medium or a transparent recording medium, it may be necessary to conceal the base in order to improve the color development of the printed matter. In order to conceal the base, a concealing white ink is generally used, and in such white inks, inorganic pigments with high concealing properties, particularly titanium oxide, are commonly used as the pigment.

[0004] Patent Document 1 discloses an aqueous white dispersion in which titanium oxide is dispersed using a dispersant, and describes that the dispersion has dispersion stability over time that inhibits the settling of pigment particles and can form a white ink layer with good whiteness.

[0005] Patent Document 2 discloses a method for producing a white microparticle aqueous dispersion, which includes a step of mixing white microparticles (titanium oxide) and a polymer dispersant in an aqueous medium to obtain a microparticle aqueous dispersion, and a step of adding a polymerizable monomer to the obtained microparticle dispersion and polymerizing it to obtain a white microparticle aqueous dispersion. It also describes that by using this white microparticle aqueous dispersion, a water-based ink that can achieve both ink ejection stability and gloss of the obtained printed matter can be obtained. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2021-105087 A [Patent Document 2] JP 2019-73595 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the embodiments of the present invention is to provide a method for producing an aqueous dispersion that can be used to obtain an aqueous ink with high whiteness, an aqueous dispersion that can be used to obtain an aqueous ink with high whiteness, and an aqueous ink with high whiteness. [Means for solving the problem]

[0008] One embodiment of the present invention relates to a method for producing an aqueous dispersion comprising: step 1 obtaining a titanium oxide aqueous dispersion containing titanium oxide particles, a dispersant, and water; and step 2 adding a polymerizable monomer and a polymerization initiator to the titanium oxide aqueous dispersion to polymerize the polymerizable monomer to obtain titanium oxide composite particles, wherein step 2 comprises adding the polymerizable monomer at once in an amount of 1 / 5 or more of the total amount of the titanium oxide particles by mass ratio, and the polymerizable monomer comprises polymerizable monomer A having a solubility in water of 0.5 g / 100 ml or less at 23° C. Another embodiment of the present invention relates to an aqueous dispersion containing raspberry-shaped titanium oxide composite particles including titanium oxide particles and a resin coating the surfaces of the titanium oxide particles, and water. Another embodiment of the present invention relates to an aqueous ink comprising raspberry-shaped titanium oxide composite particles comprising titanium oxide particles and a resin coating the surfaces of the titanium oxide particles, and water. Effect of the Invention

[0009] According to embodiments of the present invention, it is possible to provide a method for producing an aqueous dispersion that can be used to obtain an aqueous ink with high whiteness, an aqueous dispersion that can be used to obtain an aqueous ink with high whiteness, and an aqueous ink with high whiteness. [Brief description of the drawings]

[0010] [Figure 1A] 1 is an electron microscope photograph of an example of raspberry-shaped titanium oxide composite particles. [Figure 1B] 1 is an electron microscope photograph of an example of raspberry-shaped titanium oxide composite particles. [Figure 2A] 1 is an electron microscope photograph of an example of non-raspberry-shaped titanium oxide composite particles. [Figure 2B] 1 is an electron microscope photograph of an example of non-raspberry-shaped titanium oxide composite particles. [Figure 3A] 1 is an electron microscope photograph of an example of titanium oxide particles when titanium oxide is dispersed using a dispersant. [Figure 3B] 1 is an electron microscope photograph of an example of titanium oxide particles when titanium oxide is dispersed using a dispersant. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the present invention will be described using embodiments. The examples in the following embodiments do not limit the present invention. In the following description, "water-based ink" may be simply referred to as "ink".

[0012] <Method of manufacturing aqueous dispersion> The method for producing an aqueous dispersion according to the embodiment includes step 1 of obtaining an aqueous titanium oxide dispersion containing titanium oxide particles, a dispersant, and water, and step 2 of adding a polymerizable monomer and a polymerization initiator to the aqueous titanium oxide dispersion to polymerize the polymerizable monomer to obtain titanium oxide composite particles, wherein step 2 includes a step of adding, all at once, a polymerizable monomer in a mass ratio of 1 / 5 or more of the total amount of titanium oxide particles, and the polymerizable monomer includes polymerizable monomer A having a solubility in water of 0.5 g / 100 ml or less at 23° C.

[0013] The aqueous dispersion obtained by the method for producing an aqueous dispersion according to the embodiment can be used to obtain an aqueous ink having a high whiteness. The reason for this is believed to be as follows, but the scope of the present invention is not limited to the theory described below. In the method for producing the aqueous dispersion according to the embodiment, in step 2, a polymerizable monomer and a polymerization initiator are added to the titanium oxide aqueous dispersion to polymerize the polymerizable monomer and obtain titanium oxide composite particles, and a polymerizable monomer containing a polymerizable monomer A having a solubility in water of 0.5 g / 100 ml or less at 23° C. is used. Step 2 also includes a step of adding a polymerizable monomer in an amount of 1 / 5 or more by mass ratio to the total amount of titanium oxide particles in the titanium oxide aqueous dispersion. Here, since the polymerizable monomer containing the polymerizable monomer A, which has low solubility in water, is relatively abundant relative to the surface area of ​​the titanium oxide particles, resin particles are easily formed by polymerization of the polymerizable monomer. It is presumed that these resin particles gather in a raspberry shape on the surface of the titanium oxide particles to form raspberry-shaped titanium oxide composite particles. It is considered that the surface area is increased due to the raspberry-shaped particle shape, thereby improving the reflectance of visible light and improving the whiteness. FIG. 1A and FIG. 1B show electron microscope photographs of an example of raspberry-shaped titanium oxide composite particles. For comparison, electron microscope photographs of an example of non-raspberry-shaped titanium oxide composite particles are shown in Figures 2A and 2B, and for further comparison, electron microscope photographs of an example of titanium oxide particles in which titanium oxide is dispersed using a dispersant are shown in Figures 3A and 3B.

[0014] In addition, since inorganic pigments such as titanium oxide have a high specific gravity, when used in inks with relatively low viscosity such as inkjet inks, suppressing pigment sedimentation may be an issue. If the particle size of titanium oxide is reduced in order to suppress pigment sedimentation, the white coloring tends to decrease. If the method for producing an aqueous dispersion according to the embodiment is used, pigment sedimentation can also be suppressed. This is presumably because titanium oxide composite particles have a lower density than particles of titanium oxide alone, making particle sedimentation easier to suppress. In addition, if pigment particles sediment, a cake layer may be formed by the sedimented particles, reducing redispersibility. However, in the aqueous dispersion produced by the production method according to the embodiment, the formation of a cake by the sedimented particles is also suppressed, and redispersibility tends to be excellent.

[0015] Step 1 for obtaining a titanium oxide aqueous dispersion containing titanium oxide particles, a dispersant and water will be described.

[0016] The titanium oxide particles are not particularly limited. Titanium oxide has a crystal structure of rutile type (tetragonal), anatase type (tetragonal), or brookite type (orthorhombic). From the viewpoints of crystal stability, hiding power, and availability, rutile type titanium oxide is preferred.

[0017] The titanium oxide particles may be untreated, but from the viewpoint of obtaining good dispersibility, surface-treated titanium oxide particles are preferred. Examples of surface treatment of titanium oxide particles include surface treatment with an inorganic substance, surface treatment with an organic substance such as a titanium coupling agent, a silane coupling agent, or silicone oil, and surface treatment with an inorganic substance is preferred.

[0018] Examples of the surface treatment of titanium oxide particles with an inorganic substance include a method of treating the surface with one or more materials selected from alumina (Al2O3), silica (SiO2), zinc oxide (ZnO), zirconia (ZrO2), magnesium oxide (MgO), and the like.

[0019] Since titanium oxide particles have the ability to decompose organic matter due to photocatalytic activity, it is preferable to treat the titanium oxide particle surface with alumina or the like from the viewpoints of suppressing photocatalytic activity and improving the wetting of titanium oxide during dispersion. Moreover, from the viewpoints of adjusting the acid-base state of the titanium oxide particle surface and improving weather resistance, it is also possible to treat the surface in combination with silica. From the viewpoint of the strength of the surface treatment layer, alumina is preferable because it is stronger than silica. From the above viewpoints, the titanium oxide particles are more preferably treated with at least one selected from alumina, silica, zinc oxide and zirconia, even more preferably treated with at least one selected from alumina and silica, and particularly preferably treated with at least alumina. The titanium oxide particles may be, for example, titanium oxide particles whose surface has been treated with alumina, or titanium oxide particles whose surface has been treated with silica and alumina.

[0020] The primary particle diameter of the titanium oxide particles is preferably 150 nm or more, 180 nm or more, 200 nm or more, or 250 nm or more, and is preferably 400 nm or less, 350 nm or less, 300 nm or less, or 280 nm or less. The primary particle diameter of the titanium oxide particles may be, for example, 150 to 400 nm, 150 to 350 nm, 180 to 300 nm, 200 to 300 nm, or 250 to 280 nm. The primary particle diameter of the titanium oxide particles is the arithmetic average particle diameter based on the number of particles obtained from an image taken with an electron microscope. Specifically, it is calculated using the major axis of each particle. The same applies to the primary particle diameter of the titanium oxide particles below.

[0021] The dispersant is not particularly limited, and examples thereof include polymer dispersants and surfactant-type dispersants. From the viewpoint of dispersion stability, the dispersant is preferably a polymer dispersant. The weight average molecular weight of the polymer dispersant is preferably 3,000 or more, more preferably 5,000 or more. The weight average molecular weight of the polymer dispersant is, for example, preferably 3,000 to 50,000, more preferably 5,000 to 30,000. In the present disclosure, the weight average molecular weight is a value obtained by gel permeation chromatography (GPC) analysis in terms of polystyrene. From the viewpoint of forming raspberry-shaped titanium oxide composite particles, a dispersant having an acidic group is preferred. By using a dispersant having an acidic group, it is easy to make the titanium oxide particle surface anionic, and it is presumed that, for example, when the resin particles are cationic, they are adsorbed on the anionic titanium oxide particles to easily obtain raspberry-shaped titanium oxide composite particles. As the dispersant having an acidic group, a polymer dispersant having an acidic group is preferred. Examples of the acidic group include a carboxyl group, a sulfo group, and a phosphate group.

[0022] Examples of polymer dispersants having an acidic group include isobutylene-maleic acid copolymers, aromatic sulfonic acid-formaldehyde condensates, polycarboxylic acid polymers, and salts thereof. Examples of commercially available isobutylene-maleic acid copolymers include "ISOBAN-600" manufactured by Kuraray Co., Ltd. Examples of polymer dispersants having an acidic group include sodium salts of "ISOBAN-600". Examples of commercially available sodium salts of aromatic sulfonic acid-formaldehyde condensates include "Demol N" manufactured by Kao Corporation. Examples of commercially available polycarboxylic acid polymers and their salts include "Demol EP" manufactured by Kao Corporation.

[0023] In the titanium oxide aqueous dispersion obtained in step 1, the content of the dispersant is preferably 0.01 to 2.0% by mass, and more preferably 0.1 to 1.0% by mass, based on the titanium oxide particles.

[0024] The water is not particularly limited, but it is preferable to use water that contains as few ionic components as possible. Examples of water include purified water, ion-exchanged water, distilled water, and ultrapure water.

[0025] The titanium oxide aqueous dispersion obtained in step 1 may contain other components, such as a pH adjuster and a preservative.

[0026] In step 1, the method for obtaining a titanium oxide aqueous dispersion containing titanium oxide, a dispersant, and water is not particularly limited, and can be appropriately produced by, for example, a known method. For example, all the components are charged into a stirrer or the like at once or in portions, and dispersed to obtain the titanium oxide aqueous dispersion. After that, water, for example, may be further added. The average particle size (dispersed particle size) of titanium oxide particles in the titanium oxide aqueous dispersion is preferably from 200 to 500 nm, and more preferably from 250 to 450 nm. The average particle size (dispersed particle size) of titanium oxide particles in a titanium oxide aqueous dispersion is a volume-based average particle size measured using dynamic light scattering (DLS). The same applies to the average particle size (dispersed particle size) of titanium oxide particles in a titanium oxide aqueous dispersion below.

[0027] Hereinafter, step 2 in which a polymerizable monomer and a polymerization initiator are added to a titanium oxide aqueous dispersion to polymerize the mixture to obtain titanium oxide composite particles will be described.

[0028] In step 2, one or more polymerizable monomers can be used. As the polymerizable monomer, a monomer having a polymerizable group can be used. Examples of the polymerizable group include a vinyl group, an allyl group, an isopropenyl group, and a (meth)acryloyl group. Examples of the polymerizable monomer include a (meth)acrylate monomer, an aromatic group-containing monomer, and a heterocycle-containing monomer. The (meth)acryloyl group means an acryloyl group, a methacryloyl group, or both of these. The (meth)acrylate means a methacrylate, an acrylate, or both of these.

[0029] Examples of the (meth)acrylate monomer include (meth)acrylates having an alkyl group having 1 to 12 carbon atoms, such as methyl, ethyl, propyl, butyl, 2-ethylhexyl, and dodecyl; alicyclic (meth)acrylates having a group having an alicyclic structure, such as an alkyl group of the formula, such as isobornyl and cyclohexyl; and aromatic group-containing (meth)acrylates, which are given as examples of aromatic group-containing monomers described later.

[0030] Examples of aromatic group-containing monomers include styrene-based monomers such as styrene, 2-methylstyrene, α-methylstyrene, and vinyltoluene; and aromatic group-containing (meth)acrylates such as phenyl(meth)acrylate, benzyl(meth)acrylate, phenoxyethyl(meth)acrylate, 1-naphthyl(meth)acrylate, and ethoxylated-o-phenylphenol acrylate.

[0031] Examples of heterocycle-containing monomers include vinylpyridine, vinylcarbazole, and vinylpyrrolidone.

[0032] In step 2, one or more polymerizable monomers can be used. The amount of the polymerizable monomer used is preferably 0.2 to 10, more preferably 0.3 to 2, and even more preferably 0.5 to 1.5, relative to 1 part of the titanium oxide particles in terms of mass ratio.

[0033] From the viewpoint of forming raspberry-shaped titanium oxide composite particles, it is preferable to use a polymerizable monomer A having a solubility in water of 0.5 g / 100 ml or less at 23° C. in step 2. The solubility of the polymerizable monomer A in water at 23° C. is preferably 0.5 g / 100 ml or less, more preferably 0.3 g / 100 ml or less, and even more preferably is substantially insoluble. Examples of the polymerizable monomer A include styrene, benzyl (meth)acrylate, butyl (meth)acrylate, and vinyl carbazole.

[0034] As the polymerizable monomer, from the viewpoint of further improving the whiteness of the aqueous ink, a polymerizable monomer capable of obtaining a resin having a high refractive index such as polystyrene is preferable. Examples of such polymerizable monomers include the above-mentioned styrene, benzyl (meth)acrylate, vinyl carbazole, etc. From the viewpoint of further improving redispersibility, polymerizable monomers capable of obtaining a resin having a low specific gravity, a high glass transition temperature (Tg), and hydrophobicity are preferred. From this viewpoint, styrene, benzyl (meth)acrylate, vinyl carbazole, etc. are preferred.

[0035] The polymerizable monomer A may be used alone or in combination of two or more kinds. The total amount of the polymerizable monomers used in step 2 may be polymerizable monomer A, or a combination of polymerizable monomer A and other polymerizable monomers may be used. The polymerizable monomer A is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more, based on the total amount of polymerizable monomers. The polymerizable monomer A may be, for example, 100% by mass or less, based on the total amount of polymerizable monomers. The polymerizable monomer A may be 30 to 100% by mass, 50 to 100% by mass, or 70 to 100% by mass, based on the total amount of polymerizable monomers.

[0036] As the polymerization initiator, any of those generally used for emulsion polymerization can be used, but it is preferable to use a water-soluble polymerization initiator. Specific examples of the polymerization initiator include persulfates such as potassium persulfate and ammonium persulfate, organic peroxides such as hydrogen peroxide and t-butyl hydroperoxide, and azo polymerization initiators such as 4,4'-azobis(4-cyanovaleric acid), 2,2-azobis(2-amidinopropane) dihydrochloride, and 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] tetrahydrate. As the polymerization initiator, a redox initiator in which the polymerization initiator and a reducing agent are used in combination as described above can also be used. As the reducing agent, sodium sulfoxylate formaldehyde, ascorbic acid, sulfite, tartaric acid or a salt thereof, etc. can be used.

[0037] From the viewpoint of forming raspberry-shaped titanium oxide composite particles, the polymerization initiator is preferably an anionic polymerization initiator, a nonionic polymerization initiator, or a polymerization initiator having an amphoteric ion structure, and more preferably a polymerization initiator having an amphoteric ion structure. When using a polymerization initiator having an amphoteric ion structure, an amphoteric functional group is introduced into the obtained resin particles, and these resin particles become cationic in an acidic to neutral environment, and are likely to be adsorbed to an anionic surface. For this reason, for example, when an acidic group derived from a dispersant or the like is present on the titanium oxide particle surface, it is presumed that the resin particles obtained by polymerization are likely to be adsorbed to the titanium oxide particles, and raspberry-shaped composite particles are likely to be obtained.

[0038] The polymerization initiator may be used alone or in combination of two or more kinds. The amount of the polymerization initiator used is preferably 0.01 to 10% by mass, more preferably 0.05 to 5% by mass, and further preferably 0.1 to 2% by mass, based on the polymerizable monomer.

[0039] Step 2 can include a step of adding a polymerizable monomer in a mass ratio of 1 / 5 or more to the total amount of titanium oxide particles at one time (hereinafter, also referred to as step 2X). In this step 2X, the polymerizable monomer in a mass ratio of 1 / 5 or more to the total amount of titanium oxide particles in the titanium oxide aqueous dispersion is added at one time, rather than being added in several divided portions or continuously added by continuous dropwise addition, etc. The polymerizable monomer added in step 2X may be the entire amount of the polymerizable monomer added in step 2, or may be a part thereof. The amount of the polymerizable monomer added in step 2X is preferably 1 / 5 or more, more preferably 1.5 / 5 or more, and even more preferably 2 / 5 or more, based on the total amount of titanium oxide particles. The amount of the polymerizable monomer added in step 2X may be, for example, 10 / 5 or less, 5 / 5 or less, 4 / 5 or less, or 3 / 5 or less, based on the total amount of titanium oxide particles. The amount of the polymerizable monomer added in step 2X may be, for example, 1 / 5 to 10 / 5, 1 / 5 to 5 / 5, 1.5 / 5 to 4 / 5, or 2 / 5 to 3 / 5, based on the total amount of titanium oxide particles.

[0040] In step 2, raspberry-shaped titanium oxide composite particles can be obtained, which is believed to be an aqueous dispersion that can be used to obtain an aqueous ink with high whiteness. On the other hand, if step 2X is not included in step 2 and, for example, the entire amount of polymerizable monomer is continuously dropped, raspberry-shaped particles cannot be obtained. This is presumably because the polymerization of the polymerizable monomer gradually progresses and a thin resin layer gradually grows on the surface of the titanium oxide.

[0041] In step 2, a surfactant may further be added. The surfactant can be used, for example, by adsorbing onto the surface of titanium oxide particles to modify the particle surface, suppressing aggregation, making the particle surface hydrophobic, imparting ionicity to the particle surface, etc. The surfactant may also be used as a starting point for polymerization of a polymerizable monomer. The surfactant can also be used to enhance the stability of polymerization. Examples of the surfactant include anionic surfactants, nonionic surfactants, cationic surfactants, amphoteric surfactants, and polymeric surfactants. The surfactant is preferably anionic or nonionic surfactants. In addition, the cloud point of the surfactant can be utilized to increase the efficiency of adsorption of the surfactant onto particles, for example by dissolving the surfactant at a temperature below the cloud point and then precipitating the surfactant on the surface of the particles by raising the temperature to the cloud point or higher.

[0042] For example, from the viewpoint of polymerizing a polymerizable monomer starting from the surfactant, it is preferable to use a surfactant having a polymerizable group, such as a vinyl group, an allyl group, an isopropenyl group, or a (meth)acryloyl group.

[0043] Examples of anionic surfactants having a polymerizable group include bis(polyoxyethylene polycyclic phenyl ether) methacrylate sulfonate salts (e.g., "Antox MS-60" manufactured by Nippon Nyukazai Co., Ltd.), propenyl-alkyl sulfosuccinate salts, polyoxyethylene (meth)acrylate sulfonate salts, polyoxyethylene (meth)acrylate phosphonate salts (e.g., "Eleminol RS-30" manufactured by Sanyo Chemical Industries, Ltd.), polyoxyethylene alkylpropenyl phenyl ether sulfonate salts (e.g., "Aqualon HS-10" manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and sulfone salts of allyloxymethyl alkyloxy polyoxyethylene. Examples of such esters include aryloxymethyl nonylphenoxyethyl hydroxypolyoxyethylene sulfate salts (e.g., Adeka Reasoap SE-10 manufactured by ADEKA Corporation), allyloxymethyl alkoxyethyl hydroxypolyoxyethylene sulfate salts (e.g., Adeka Reasoap SR-10, Adeka Reasoap SR-30 manufactured by ADEKA Corporation), and polyoxyethylene styrenated propenyl phenyl ether sulfate ammonium salts (e.g., Adeka Reasoap AR-10, Adeka Reasoap AR-20, Adeka Reasoap AR-30 manufactured by ADEKA Corporation). Examples of nonionic surfactants having a polymerizable group include allyloxymethylalkoxyethylhydroxypolyoxyethylene (e.g., ADEKA REASOAP ER-20, etc., manufactured by ADEKA CORPORATION), polyoxyethylene alkylpropenylphenyl ether (e.g., Aqualon RN-20, etc., manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.), allyloxymethylnonylphenoxyethylhydroxypolyoxyethylene (e.g., ADEKA REASOAP NE-10, etc., manufactured by ADEKA CORPORATION), and polyoxyethylene styrenated propenylphenyl ether (e.g., Aqualon AN-10, Aqualon AN-20, Aqualon AN-30, Aqualon AN-5065, etc., manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.). When environmental considerations are particularly important, it is more preferable to use non-nonylphenyl type surfactants.

[0044] Examples of anionic surfactants not having a polymerizable group include alkyl sulfate salts such as ammonium dodecyl sulfate, sodium dodecyl sulfate (sodium dodecyl sulfate), etc.; alkyl sulfonate salts such as ammonium dodecyl sulfonate, sodium dodecyl sulfonate, etc.; alkyl aryl sulfonate salts such as ammonium dodecyl benzene sulfonate, sodium dodecyl naphthalene sulfonate, etc.; polyoxyethylene alkyl sulfate salts; polyoxyethylene alkyl aryl sulfate salts; dialkyl sulfosuccinates; aryl sulfonic acid formalin condensates; fatty acid salts such as ammonium laurate, sodium stearylate, etc. Examples of nonionic surfactants having no polymerizable group include polyoxyethylene alkyl ethers; polyoxyethylene alkylaryl ethers; condensates of polyethylene glycol and polypropylene glycol; sorbitan fatty acid esters; polyoxyethylene sorbitan fatty acid esters; fatty acid monoglycerides; polyamides; and condensation products of ethylene oxide and aliphatic amines. Examples of cationic surfactants having no polymerizable group include alkyl ammonium salts such as dodecyl ammonium chloride. Examples of amphoteric surfactants having no polymerizable group include betaine ester emulsifiers. Examples of polymeric surfactants that do not have a polymerizable group include poly(meth)acrylates such as sodium polyacrylate; polyvinyl alcohol; polyvinylpyrrolidone; polyhydroxyalkyl(meth)acrylates such as polyhydroxyethyl acrylate; and copolymers in which one or more of the polymerizable monomers that constitute these polymers are copolymerization components.

[0045] The surfactants may be used alone or in combination of two or more. The amount of the surfactant used is preferably from 0.01 to 10% by mass, more preferably from 0.05 to 8% by mass, and even more preferably from 0.1 to 5% by mass, based on the polymerizable monomer.

[0046] In step 2, for example, a polymerizable monomer, a polymerization initiator, and, if necessary, a surfactant, etc. can be added to the titanium oxide aqueous dispersion obtained in step 1 to polymerize the polymerizable monomer.

[0047] Step 2 includes step 2X of adding polymerizable monomer at a time in an amount of 1 / 5 or more by mass based on the total amount of titanium oxide particles, but the remainder of the polymerizable monomer may be added at a time, in portions, or continuously. The polymerization initiator and surfactant, which are added as needed, may each be added at a time, in portions, or continuously. For example, in step 2, the polymerizable monomer, polymerization initiator, and optionally surfactant may be added all at once to carry out the polymerization reaction, or may be added in two or more portions to carry out two or more stages of polymerization reaction. For example, a portion of each of the polymerizable monomer, polymerization initiator, and optionally surfactant may be added all at once to the titanium oxide aqueous dispersion or its dilution to carry out the polymerization reaction in the first stage, and then the remaining portions of the polymerizable monomer, polymerization initiator, and optionally surfactant may be added all at once to carry out the polymerization reaction in the second stage. In this case, the amount of polymerizable monomer added in either the first stage or the second stage may be 1 / 5 or more of the total amount of titanium oxide particles. The polymerization conditions can be appropriately adjusted depending on the monomers, polymerization initiators, etc. used. The polymerization temperature is, for example, preferably 30 to 150° C., and more preferably 50 to 120° C. The polymerization time is preferably 10 to 20 hours, and more preferably 1 to 10 hours. When polymerization is carried out in two or more stages, the polymerization time for one stage may be 10 minutes to 20 hours or 1 to 10 hours.

[0048] After the polymerizable monomer is polymerized as described above, filtration, centrifugation, addition of water, etc. may be carried out as necessary.

[0049] As described above, a resin is synthesized by polymerization of the polymerizable monomer, and an aqueous dispersion of titanium oxide composite particles containing titanium oxide particles and a resin can be obtained. In the titanium oxide composite particles, the resin synthesized by polymerization of the polymerizable monomer may be, for example, a homopolymer of polymerizable monomer A, a copolymer of two or more types of polymerizable monomer A, or a copolymer of one or more types of polymerizable monomer A and other polymerizable monomers.

[0050] In the titanium oxide composite particles, the resin obtained by polymerization of the polymerizable monomer preferably covers the surface of the titanium oxide particles. The resin may cover at least a part of the surface of the titanium oxide particles. The resin may cover only a part of the surface of the titanium oxide particles, or the entire surface of the titanium oxide particles. In the titanium oxide composite particles, the resin preferably has the shape of resin particles. The titanium oxide composite particles are preferably raspberry-shaped titanium oxide composite particles containing titanium oxide particles and a resin that covers the surfaces of the titanium oxide particles. In the titanium oxide composite particles, the average particle diameter of the titanium oxide particles may be, for example, 150 to 400 nm, 150 to 350 nm, 180 to 300 nm, 200 to 300 nm, or 250 to 280 nm. In addition, in the titanium oxide composite particles, the resin preferably has a shape of resin particles with an average particle diameter of 10 to 200 nm, and more preferably has an average particle diameter of 50 to 180 nm. The average particle size of the titanium oxide particles and the resin particles in the titanium oxide composite particles is the arithmetic mean diameter based on the number of particles obtained from an image by an electron microscope. Specifically, it is calculated using the diameter of a circle having the same area as the projected area of ​​the particle image (circle equivalent diameter). The same applies to the average particle size of the titanium oxide particles and the resin particles in the titanium oxide composite particles below.

[0051] In the aqueous dispersion thus obtained, the titanium oxide content is preferably from 1 to 50% by mass, more preferably from 10 to 40% by mass, and even more preferably from 20 to 30% by mass, based on the total amount of the aqueous dispersion. In the aqueous dispersion, the titanium oxide composite particles preferably account for 20 to 80 mass %, more preferably 30 to 70 mass %, and even more preferably 40 to 60 mass %, in terms of the total amount of the titanium oxide particles and the polymerizable monomer, which are the constituent materials of the titanium oxide composite particles, relative to the total amount of the aqueous dispersion.

[0052] In the method for producing the aqueous dispersion, other components may be further used, such as a pH adjuster, a preservative, an anti-rust agent, and an antifoaming agent.

[0053] The viscosity of the aqueous dispersion obtained by the above method is preferably 1 to 20 mPa·s at 23°C. The average particle size (dispersed particle size) of the titanium oxide composite particles in the aqueous dispersion obtained by the above method is preferably from 300 to 600 nm, and more preferably from 350 to 550 nm. The average particle size (dispersed particle size) of the titanium oxide composite particles in the aqueous dispersion is the volume-based average particle size measured using dynamic light scattering (DLS). The same applies to the average particle size (dispersed particle size) of the titanium oxide composite particles in the aqueous dispersion below.

[0054] <Water dispersion> The aqueous dispersion according to one embodiment is an aqueous dispersion containing raspberry-shaped titanium oxide composite particles containing titanium oxide particles and a resin coating the surfaces of the titanium oxide particles, and water. This aqueous dispersion can be used to obtain an ink with high whiteness. In addition, the pigment sedimentation is suppressed, and the aqueous dispersion has excellent redispersibility.

[0055] In the titanium oxide composite particles, the titanium oxide particles may be, for example, the titanium oxide particles described in the above-mentioned method for producing the aqueous dispersion.

[0056] In the titanium oxide composite particles, the resin may be, for example, a resin obtainable by polymerizing one or more of the polymerizable monomers in step 2 of the above-mentioned method for producing an aqueous dispersion. The resin is preferably a resin containing units derived from one or more of the above-mentioned polymerizable monomers.

[0057] In the titanium oxide composite particles, the resin preferably contains the above-mentioned unit derived from the polymerizable monomer A. The unit derived from the polymerizable monomer A may be one or more kinds contained in the resin. The amount of the unit derived from the polymerizable monomer A relative to the total amount of the polymerizable monomers used to constitute the resin is preferably 30% by mass or more, more preferably 50% by mass or more, and even more preferably 70% by mass or more. The amount of the unit derived from the polymerizable monomer A relative to the total amount of the polymerizable monomers used to constitute the resin may be, for example, 100% by mass or less. The amount of the unit derived from the polymerizable monomer A relative to the total amount of the polymerizable monomers used to constitute the resin may be 30 to 100% by mass, 50 to 100% by mass, or 70 to 100% by mass.

[0058] In the titanium oxide composite particles, the resin may be, for example, a homopolymer of polymerizable monomer A, a copolymer of two or more types of polymerizable monomer A, or a copolymer of one or more types of polymerizable monomer A and other polymerizable monomers.

[0059] In the titanium oxide composite particles, the resin may cover at least a part of the surface of the titanium oxide particles. The resin may cover only a part of the surface of the titanium oxide particles, or the entire surface of the titanium oxide particles. In the titanium oxide composite particles, the resin preferably has the shape of resin particles.

[0060] In the titanium oxide composite particles, the average particle diameter of the titanium oxide particles may be, for example, 150 to 400 nm, 150 to 350 nm, 180 to 300 nm, 200 to 300 nm, or 250 to 280 nm. In addition, in the titanium oxide composite particles, the resin preferably has a shape of resin particles with an average particle diameter of 10 to 200 nm, and more preferably has an average particle diameter of 50 to 180 nm.

[0061] In the titanium oxide composite particles, the amount of resin, as the total amount of monomers constituting the resin, is preferably 0.2 to 10, more preferably 0.3 to 2, and even more preferably 0.5 to 1.5, in mass ratio relative to 1 titanium oxide particle.

[0062] In the aqueous dispersion, the content of titanium oxide is preferably from 1 to 50% by mass, more preferably from 10 to 40% by mass, and further preferably from 20 to 30% by mass, based on the total amount of the aqueous dispersion. In the aqueous dispersion, the titanium oxide composite particles preferably account for 20 to 80 mass %, more preferably 30 to 70 mass %, and even more preferably 40 to 60 mass %, of the total amount of the titanium oxide particles and monomers constituting the resin, relative to the total amount of the aqueous dispersion.

[0063] The water is not particularly limited, but it is preferable to use water that contains as few ionic components as possible. Examples of water include purified water, ion-exchanged water, distilled water, and ultrapure water.

[0064] The aqueous dispersion may further contain other components, such as those listed in the method for producing the aqueous dispersion described above.

[0065] This aqueous dispersion can be produced, for example, by the above-mentioned method for producing an aqueous dispersion. The viscosity of the aqueous dispersion at 23°C is preferably 1 to 20 mPa·s. The average particle size (dispersed particle size) of the titanium oxide composite particles in the water dispersion is preferably from 300 to 600 nm, and more preferably from 350 to 550 nm.

[0066] <Water-based ink> The water-based ink according to one embodiment is a water-based ink containing raspberry-shaped titanium oxide composite particles containing titanium oxide particles and a resin coating the surfaces of the titanium oxide particles, and water. This ink can be used as, for example, a white ink.

[0067] The titanium oxide particles, the resin coating the surfaces of the titanium oxide particles, and the titanium oxide composite particles are each as described above in the aqueous dispersion.

[0068] In the aqueous ink, the content of titanium oxide is preferably 0.1 to 30% by mass, more preferably 1 to 20% by mass, and even more preferably 1 to 15% by mass, based on the total amount of the ink. In the aqueous ink, the titanium oxide composite particles preferably account for 2 to 50 mass % of the total amount of the ink, in terms of the total amount of the titanium oxide particles and monomers constituting the resin, more preferably 5 to 40 mass %, and even more preferably 5 to 30 mass %.

[0069] The water is not particularly limited, but it is preferable to use water that contains as few ionic components as possible. Examples of water include purified water, ion-exchanged water, distilled water, and ultrapure water. In the aqueous ink, the content of water is preferably 40 to 90% by mass, and more preferably 50 to 80% by mass, based on the total amount of the ink.

[0070] It is preferable to blend a water-dispersible resin in the water-based ink. A water-dispersible resin is a resin particle that can be dispersed in an aqueous solvent. The water-dispersible resin exhibits water dispersibility and can be dispersed in water without dissolving in water to form an oil-in-water (O / W) emulsion. The water-dispersible resin is preferably contained in the aqueous ink in a dispersed state as resin particles. The water-dispersible resin can be blended as a resin emulsion when producing the aqueous ink.

[0071] Examples of the water-dispersible resin include: Conjugated diene resins such as styrene-butadiene copolymers, methyl methacrylate-butadiene copolymers, and vinyl chloride-vinyl acetate copolymers; (Meth)acrylic resins such as polymers of acrylic acid esters and methacrylic acid esters, or copolymers thereof with styrene or the like; Vinyl resins such as ethylene-vinyl acetate copolymers, Or functional group-modified resins of these various resins using monomers containing functional groups such as carboxyl groups; Examples of the aqueous resin emulsion include melamine resin, urea resin, polyurethane resin, polyester resin, polyolefin resin, silicone resin, polyvinyl butyral resin, alkyd resin, etc. A resin emulsion of a single resin of these may be used, or a hybrid type resin emulsion may be used. (Meth)acrylic means methacrylic, acrylic, or both of these.

[0072] These water-dispersible resins may be used alone or in combination of two or more. The content of the water-dispersible resin in the ink is preferably 0.5 to 30% by mass, and more preferably 1 to 20% by mass.

[0073] It is preferable to blend a water-soluble organic solvent in the ink. As the water-soluble organic solvent, an organic compound that is liquid at room temperature and dissolves in water can be used, and it is preferable to use a water-soluble organic solvent that is uniformly mixed with the same volume of water at 20°C under 1 atmosphere. For example, lower alcohols such as methanol, ethanol, 1-propanol, isopropanol, 1-butanol, 2-butanol, isobutanol, and 2-methyl-2-propanol; glycols such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, polyethylene glycol, propylene glycol, dipropylene glycol, tripropylene glycol, and polypropylene glycol; glycerins such as glycerin, diglycerin, triglycerin, and polyglycerin; acetins such as monoacetin and diacetin; ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, diethyl ether, ethyl ... Glycol ethers such as ethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, triethylene glycol monomethyl ether, triethylene glycol monoethyl ether, triethylene glycol monopropyl ether, triethylene glycol monobutyl ether, tetraethylene glycol monomethyl ether, tetraethylene glycol monoethyl ether, tetraethylene glycol dimethyl ether, and tetraethylene glycol diethyl ether; triethanolamine, 1-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, β-thiodiglycol, and sulfolane can be used. The boiling point of the water-soluble organic solvent is preferably 100° C. or higher, and more preferably 150° C. or higher.

[0074] These water-soluble organic solvents may be used alone, or two or more kinds may be used in combination as long as they form a single phase with water. When two or more kinds of water-soluble organic solvents are used, the total content of the water-soluble organic solvents in the ink is preferably 5 to 50% by mass, and more preferably 10 to 35% by mass.

[0075] The water-based ink preferably contains a surfactant. As the surfactant, an anionic surfactant, a cationic surfactant, an amphoteric surfactant, a nonionic surfactant, or a combination thereof can be preferably used, and a nonionic surfactant is more preferable. In addition, either a low molecular weight surfactant or a high molecular weight surfactant may be used.

[0076] Examples of nonionic surfactants include ester-type surfactants such as glycerin fatty acid esters and fatty acid sorbitan esters, ether-type surfactants such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers and polyoxypropylene alkyl ethers, ether ester-type surfactants such as polyoxyethylene sorbitan fatty acid esters, acetylene-based surfactants, silicone-based surfactants, fluorine-based surfactants, etc. Among these, acetylene-based surfactants and silicone-based surfactants can be preferably used.

[0077] Examples of the acetylene-based surfactant include acetylene glycol-based surfactants, acetylene alcohol-based surfactants, and surfactants having an acetylene group. The acetylene glycol surfactant is a glycol having an acetylene group, preferably a glycol having a symmetrical structure with the acetylene group located in the center, and may have a structure in which ethylene oxide is added to acetylene glycol.

[0078] Commercially available acetylene surfactants include, for example, the Surfynol series manufactured by Evonik Industries Ltd., such as "Surfynol 104E," "Surfynol 104H," "Surfynol 420," "Surfynol 440," "Surfynol 465," and "Surfynol 485," and the Olfin series manufactured by Nissin Chemical Industry Co., Ltd., such as "Olfin E1004," "Olfin E1010," and "Olfin E1020" (all trade names).

[0079] Examples of silicone surfactants include polyether-modified silicone surfactants, alkyl / aralkyl-co-modified silicone surfactants, and acrylic silicone surfactants. Commercially available silicone surfactants include, for example, "Silface SAG002," "Silface 503A," and "Silface SAG008" manufactured by Nissin Chemical Industry Co., Ltd. (all trade names).

[0080] Other nonionic surfactants include polyoxyethylene alkyl ether surfactants such as the Emulgen series manufactured by Kao Corporation, including "Emulgen 102KG," "Emulgen 103," "Emulgen 104P," "Emulgen 105," "Emulgen 106," "Emulgen 108," "Emulgen 120," "Emulgen 147," "Emulgen 150," "Emulgen 220," "Emulgen 350," "Emulgen 404," "Emulgen 420," "Emulgen 705," "Emulgen 707," "Emulgen 709," "Emulgen 1108," "Emulgen 4085," and "Emulgen 2025G" (all trade names).

[0081] Examples of anionic surfactants include Kao Corporation's EMAL series, such as "EMAL 0," "EMAL 10," "EMAL 2F," "EMAL 40," and "EMAL 20C," the Neopelex series, such as "Neopelex GS," "Neopelex G-15," "Neopelex G-25," and "Neopelex G-65," the Pelex series, such as "Pelex OT-P," "Pelex TR," "Pelex CS," "Pelex TA," "Pelex SS-L," and "Pelex SS-H," and the Demol series, such as "Demol N," "Demol NL," "Demol RN," and "Demol MS" (all product names).

[0082] Examples of cationic surfactants include the Acetamine series (manufactured by Kao Corporation) such as "Acetamine 24" and "Acetamine 86", the Cortamine series (manufactured by Kao Corporation) such as "Cortamine 24P", "Cortamine 86P", "Cortamine 60W", and "Cortamine 86W", and the Sanisol series (manufactured by Kao Corporation) such as "Sanisol C" and "Sanisol B-50" (all trade names).

[0083] Examples of amphoteric surfactants include the Amphitol series manufactured by Kao Corporation, such as "Amphitol 20BS," "Amphitol 24B," "Amphitol 86B," "Amphitol 20YB," and "Amphitol 20N" (all trade names). The above-mentioned surfactants may be used alone or in combination of two or more.

[0084] The HLB value of the surfactant used in the water-based ink is preferably 10.0 or less. The surfactant used in the aqueous ink is preferably an acetylene-based surfactant such as an acetylene glycol-based surfactant, and more preferably an acetylene glycol-based surfactant.

[0085] The blending amount of the surfactant in the aqueous ink is preferably from 0.1 to 5.0% by mass, and more preferably from 0.5 to 3.0% by mass, based on the total amount of the aqueous ink.

[0086] The water-based ink may contain other components as appropriate, such as a pH adjuster and a preservative.

[0087] The viscosity of the water-based ink at 23° C. is preferably from 1 to 20 mPa·s, more preferably from 2 to 15 mPa·s, and even more preferably from 3 to 10 mPa·s.

[0088] The method for producing the aqueous ink is not particularly limited, but the desired ink can be obtained by appropriately mixing each component. For example, the obtained composition may be filtered using a filter or the like. In addition, various additives may be added appropriately. As the titanium oxide composite particles, an aqueous dispersion containing titanium oxide composite particles produced by the above-mentioned method for producing an aqueous dispersion may be used. For example, the method for producing the ink may include a step of producing an aqueous dispersion containing titanium oxide composite particles by the above-mentioned method for producing an aqueous dispersion.

[0089] In this embodiment, the recording medium is not particularly limited, and examples thereof include printing paper such as plain paper, coated paper, and special paper, cloth, inorganic sheets, films, and OHP sheets, as well as adhesive sheets having an adhesive layer on the back surface of these as a base material.

[0090] The present disclosure includes the following embodiments. <1> A step 1 of obtaining a titanium oxide aqueous dispersion containing titanium oxide particles, a dispersant, and water; and step 2 of adding a polymerizable monomer and a polymerization initiator to the titanium oxide aqueous dispersion to polymerize the polymerizable monomer to obtain titanium oxide composite particles. The step 2 includes a step of adding the polymerizable monomer at a mass ratio of 1 / 5 or more to the total amount of the titanium oxide particles at once, The polymerizable monomer includes a polymerizable monomer A having a solubility in water of 0.5 g / 100 ml or less at 23° C. Method for producing the aqueous dispersion <2> The titanium oxide composite particles are raspberry-shaped composite particles containing the titanium oxide particles and a resin coating the surfaces of the titanium oxide particles. <1> A method for producing the aqueous dispersion according to claim 1. <3> The resin has a shape of resin particles. <2> A method for producing the aqueous dispersion according to claim 1. <4> The polymerizable monomer A is 30% by mass or more based on the total amount of the polymerizable monomers. <1> ~ <3> 13. The method for producing the aqueous dispersion according to claim 12, <5> The titanium oxide particles include titanium oxide particles surface-treated with at least alumina. <1> ~ <4> 13. The method for producing the aqueous dispersion according to claim 12, <6> The dispersant includes a dispersant having an acidic group. <1> ~ <5> 13. The method for producing the aqueous dispersion according to claim 12, <7> The polymerization initiator includes a polymerization initiator having a zwitterionic structure. <1> ~ <6> 13. The method for producing the aqueous dispersion according to claim 12, <8> raspberry-shaped titanium oxide composite particles containing titanium oxide particles and a resin coating the surfaces of the titanium oxide particles; and water. <9> raspberry-shaped titanium oxide composite particles containing titanium oxide particles and a resin coating the surfaces of the titanium oxide particles; A water-based ink containing water. EXAMPLES

[0091] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples.

[0092] (1) Preparation of titanium oxide aqueous dispersions 1 and 2 In a 250 mL glass container, 30 g of purified water, 20 g of the titanium oxide powder 1 described below, and 0.25% by mass of "ISOBAN-600" (Kuraray Co., Ltd., isobutylene-maleic acid copolymer) sodium salt (NaOH neutralization degree = 0.7, polymer dispersant having an acidic group) relative to the titanium oxide powder 1 were added and stirred, and then 135 g of zirconia beads having a diameter of 0.5 mm were added and treated with a pot mill rotor at a rotation speed of 100 rpm for 4 hours, and the beads were separated to obtain titanium oxide aqueous dispersion 1. Titanium oxide aqueous dispersion 2 was obtained in the same manner as in the production of titanium oxide aqueous dispersion 1, except that 20 g of titanium oxide powder 2 described below was used instead of 20 g of titanium oxide powder 1. The average particle size (dispersed particle size) of titanium oxide particles in each of the obtained titanium oxide aqueous dispersions 1 and 2 was measured by dynamic light scattering (DLS) to find that it was 340 nm for titanium oxide aqueous dispersion 1 and 330 nm for titanium oxide aqueous dispersion 2. For titanium oxide aqueous dispersions 1 and 2, and aqueous dispersions 1-R to 8-R described below, an "ELSZ-200ZS" manufactured by Otsuka Electronics Co., Ltd. was used to measure the average particle size (dispersed particle size) using DLS.

[0093] Titanium oxide powder 1: "JR-605" manufactured by Teika Corporation (titanium oxide particles surface-treated with alumina, primary particle diameter 250 nm) Titanium oxide powder 2: "CR-90" manufactured by Ishihara Sangyo Kaisha, Ltd. (titanium oxide particles surface-treated with silica and alumina, primary particle diameter 250 nm)

[0094] (2) Preparation of aqueous dispersions 1-R to 9-R Table 1 shows the materials and the amounts used in producing the aqueous dispersions 1-R to 9-R.

[0095] (2-1) Preparation of Water Dispersions 1-R to 4-R and 7-R (i) First stage Purified water was added to the titanium oxide water dispersion 1 or 2 obtained above to prepare a dispersion containing 10.0 g of titanium oxide and 0.25 mass% of "ISOBAN-600" sodium salt (NaOH neutralization degree = 0.7) in 280 g of water, and the dispersion was placed in a 500 mL four-neck flask equipped with a stirrer, a thermometer, a dropping funnel, and a reflux condenser and stirred for 10 minutes. Then, 1.0 g of an aqueous solution in which 0.025 g of sodium dodecyl sulfate was dissolved in 1.0 g of purified water was added. Next, the temperature was raised to 70 ° C., and 1.0 g of an aqueous solution containing 0.10 g of "VA-057" (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 2,2-azobis (2-amidinopropane) dihydrochloride, a polymerization initiator having an amphoteric structure) was added, and further 1.0 g of a polymerizable monomer shown in Table 1 was added and left for 60 minutes.

[0096] (ii) Second Stage Next, 3.0 g of an aqueous solution containing 0.4 g of sodium dodecyl sulfate and 1.0 g of an aqueous solution containing 0.10 g of "VA-057" were added, and 9.0 g of the polymerizable monomer shown in Table 1 was added, and the mixture was further kept at 70 ° C. for 4 hours and stirred. After cooling, the mixture was filtered through a 100 μm mesh to obtain aqueous dispersions 1-4 and 7. The obtained aqueous dispersions 1-4 and 7 were centrifuged at 4000 rpm for 15 minutes, and the supernatant was separated. Purified water was added so that titanium oxide was 25 mass % and stirred to obtain aqueous dispersions 1-R-4-R and 7-R. The average particle size (dispersed particle size) of the titanium oxide composite particles in the obtained aqueous dispersions 1-R-4-R and 7-R was measured using dynamic light scattering (DLS). In addition, a small amount of the aqueous dispersions 1-R-4-R and 7-R was freeze-dried, and the particle shape of the freeze-dried powder was observed using a scanning electron microscope (SEM). The SEM used was a JSM-7600FA manufactured by JEOL Ltd.

[0097] (2-2) Preparation of Water Dispersion 5-R (i) First stage Purified water was added to the titanium oxide aqueous dispersion 1 obtained above to prepare a dispersion containing 10.0 g of titanium oxide and 0.25 mass % of the sodium salt of "ISOBAN-600" (NaOH neutralization degree = 0.7) in 280 g of water. The dispersion was placed in a 500 mL four-neck flask equipped with a stirrer, thermometer, dropping funnel, and reflux condenser, and an aqueous solution prepared by dissolving 1.8 mg of "ADEKA REASOAP NE-10" manufactured by ADEKA CORPORATION in 1.0 g of purified water was added over the course of about 1 minute while stirring at room temperature under a nitrogen atmosphere, and the mixture was stirred for 10 minutes. After that, the temperature was raised to 55°C and further stirred for 10 minutes, after which 1.0 g of an aqueous solution in which 0.025 g of sodium dodecyl sulfate was dissolved in 1.0 g of purified water was added. Next, the temperature was raised to 70°C, and 1.0 g of an aqueous solution containing 0.10 g of "VA-057" was added, followed by 1.0 g of a polymerizable monomer shown in Table 1, and the mixture was left to stand for 60 minutes.

[0098] (ii) Second Stage Next, 3.0 g of an aqueous solution containing 0.4 g of sodium dodecyl sulfate and 1.0 g of an aqueous solution containing 0.10 g of "VA-057" were added, and 9.0 g of the polymerizable monomer shown in Table 1 was added, and the mixture was further kept at 70 ° C. for 4 hours and stirred. After cooling, the mixture was filtered through a 100 μm mesh to obtain water dispersion 5. The obtained water dispersion 5 was centrifuged at 4000 rpm for 15 minutes, and the supernatant was separated. Purified water was added so that titanium oxide was 25 mass % and stirred to obtain water dispersion 5-R. The average particle size (dispersed particle size) of the titanium oxide composite particles in the obtained water dispersion 5-R was measured using DLS. In addition, a small amount of water dispersion 5-R was freeze-dried, and the particle shape of this freeze-dried powder was observed using SEM.

[0099] (2-3) Preparation of Water Dispersion 6-R Aqueous dispersion 6 was prepared in the same manner as aqueous dispersion 1, except that "KPS" (manufactured by Fujifilm Wako Pure Chemical Industries, potassium persulfate, anionic polymerization initiator) was used instead of "VA-057" as the polymerization initiator. The obtained aqueous dispersion 6 was centrifuged at 4000 rpm for 15 minutes, and the supernatant was separated. Water was added and stirred so that titanium oxide was 25% by mass to obtain aqueous dispersion 6-R. The average particle size (dispersed particle size) of the titanium oxide composite particles in the obtained aqueous dispersion 6-R was measured using DLS. In addition, a small amount of aqueous dispersion 6-R was freeze-dried, and the particle shape of this freeze-dried powder was observed using SEM.

[0100] (2-4) Preparation of Water Dispersion 8-R Instead of "VA-057" as a polymerization initiator, "V-501" (4,4'-azobis(4-cyanovaleric acid) manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was used, the surfactant sodium dodecyl sulfate was not used, and the polymerizable monomer was added continuously at a rate of 1.25 mL / L instead of being added all at once in two separate steps, the first and second steps. Except for this, the aqueous dispersion 8 was prepared in the same manner as the aqueous dispersion 1. The obtained aqueous dispersion 8 was centrifuged at 4000 rpm for 15 minutes, the supernatant was separated, and water was added so that the titanium oxide was 25% by mass, and the mixture was stirred to obtain aqueous dispersion 8-R. The average particle size (dispersed particle size) of the titanium oxide composite particles in the obtained aqueous dispersion 8-R was measured using DLS. In addition, a small amount of the aqueous dispersion 8-R was freeze-dried, and the particle shape of this freeze-dried powder was observed using SEM.

[0101] (2-5) Preparation of water dispersion 9-R 275.6 g of purified water was added to 25.0 g of titanium oxide aqueous dispersion 1 to prepare aqueous dispersion 9. The obtained aqueous dispersion 9 was centrifuged at 4000 rpm for 15 minutes to separate the supernatant, and then purified water was added to the mixture so that the titanium oxide content was 25% by mass, followed by stirring to obtain aqueous dispersion 9-R.

[0102] Details of the sodium dodecyl sulfate and polymerizable monomers used above are as follows. Sodium dodecyl sulfate: Fujifilm Wako Pure Chemical Industries, Ltd. Styrene: Solubility in water is 0.03g / 100ml at 23℃, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. Benzyl methacrylate: Solubility in water is 0.3g / 100ml at 23℃, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. n-Butyl methacrylate: Solubility in water is 0.3g / 100ml at 23℃, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd. Methyl methacrylate: Solubility in water is 1.59g / 100ml at 23℃, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.

[0103] [Table 1]

[0104] (3) Preparation of water-based ink Each material was mixed according to the composition in Table 2, thoroughly stirred until homogenous, and then filtered through a membrane filter to prepare white inks 1 to 9 as water-based inks.

[0105] Details of the materials listed in Table 2 are as follows.

[0106] Water dispersions 1-R to 9-R: Prepared as above Water-dispersible (meth)acrylic resin: "Movinyl 6820" ((meth)acrylic resin emulsion) manufactured by Japan Coating Resins Co., Ltd. (active ingredient: 50% by mass) Glycerin: Tokyo Chemical Industry Co., Ltd. "Olfine E1010": An acetylene-based surfactant manufactured by Nissin Chemical Industry Co., Ltd.

[0107] [Table 2]

[0108] (4) Evaluation Using the water dispersions 1-R to 9-R and the white inks 1 to 9, the following evaluations were carried out.

[0109] <Dispersion stability> The viscosity of each of the aqueous dispersions 1-R to 9-R was measured and recorded as the initial value. Each of the aqueous dispersions 1-R to 9-R was placed in a sealed container and stored in a thermostatic chamber at 50°C for one month, after which the viscosity was measured and evaluated according to the following criteria. The viscosity of the aqueous dispersions 1-R to 9-R was measured at 23°C using a rheometer MCR102 (manufactured by Anton Paar). (Evaluation Criteria) A: Viscosity change rate from initial value is less than 5% B: Viscosity change rate from the initial value is 5% or more, but less than 10% C: Viscosity change rate from the initial value is 10% or more

[0110] <Redispersibility> Each of the aqueous dispersions 1-R to 9-R was placed in a sealed container and allowed to stand at room temperature for 7 days, after which it was stirred with a mix rotor for 10 minutes and visually observed whether the settled particles had been redispersed. (Evaluation Criteria) S: Redistribute everything A: Most of the material redisperses, but some sediment remains. B: Difficult to redisperse, large amount of sediment remains C: No change in sediment

[0111] <Whiteness> Each of the white inks 1 to 9 was applied to a transparent PET film using a 10 μm bar coater, dried to produce a print, and the whiteness of the print was evaluated using the L* value. Specifically, the print was placed on a uniform density plate, and the L* value was measured using a colorimeter (Videojet X-Rite eXact, Inc.) to determine the whiteness. (Evaluation Criteria) A: L* value 70 or more B:L* value 65 or more, less than 70 C:L* value less than 65

[0112] [Table 3]

[0113] As shown in Table 1, raspberry-shaped titanium oxide composite particles were formed in the aqueous dispersions 1-R to 6-R. As shown in Table 3, the white inks 1 to 6 of Examples 1 to 6 using these aqueous dispersions 1-R to 6-R were excellent in whiteness. Furthermore, the aqueous dispersions 1-R to 6-R of Examples 1 to 6 were also excellent in dispersion stability and redispersibility. In the aqueous dispersion 7 (Comparative Example 1) in which the polymerizable monomer A having a solubility in water of 0.5 g / 100 ml or less at 23° C. was not used, and the aqueous dispersion 8 (Comparative Example 2) in which the polymerizable monomer was added continuously without including a step of adding the polymerizable monomer at a mass ratio of 1 / 5 or more to the total amount of titanium oxide particles at once, the shape of the obtained titanium oxide composite particles was not raspberry-like. Furthermore, the white inks 7 and 8 of Comparative Examples 1 and 2 in which these aqueous dispersions 7-R and 8-R were used were inferior in whiteness. Furthermore, the aqueous dispersions 7-R and 8-R of Comparative Examples 1 and 2 were inferior in both dispersion stability and redispersibility. The white ink 9 using the aqueous dispersion 9-R of Comparative Example 3, which is an aqueous dispersion of titanium oxide dispersed with a dispersant, was poor in whiteness. Furthermore, the aqueous dispersion 9-R of Comparative Example 3 was poor in both dispersion stability and redispersibility.

Claims

1. Step 1 of obtaining a titanium oxide aqueous dispersion containing titanium oxide particles, a dispersant, and water; and a step 2 of adding a polymerizable monomer and a polymerization initiator to the titanium oxide aqueous dispersion to polymerize the polymerizable monomer to obtain titanium oxide composite particles. The step 2 includes a step of adding the polymerizable monomer at a mass ratio of 1 / 5 or more to the total amount of the titanium oxide particles at once, The polymerizable monomer includes a polymerizable monomer A having a solubility in water of 0.5 g / 100 ml or less at 23° C. Method for producing the aqueous dispersion

2. The method for producing an aqueous dispersion according to claim 1 , wherein the titanium oxide composite particles are raspberry-shaped composite particles comprising the titanium oxide particles and a resin coating the surfaces of the titanium oxide particles.

3. The method for producing an aqueous dispersion according to claim 2 , wherein the resin has a shape of resin particles.

4. The method for producing an aqueous dispersion according to claim 1 or 2, wherein the polymerizable monomer A is present in an amount of 30 mass % or more based on the total amount of the polymerizable monomers.

5. The method for producing an aqueous dispersion according to claim 1 or 2, wherein the titanium oxide particles include titanium oxide particles that have been surface-treated with at least alumina.

6. The method for producing an aqueous dispersion according to claim 1 or 2, wherein the dispersant comprises a dispersant having an acidic group.

7. The method for producing an aqueous dispersion according to claim 1 or 2, wherein the polymerization initiator comprises a polymerization initiator having a zwitterionic structure.

8. raspberry-shaped titanium oxide composite particles comprising titanium oxide particles and a resin coating the surfaces of the titanium oxide particles; and water.

9. raspberry-shaped titanium oxide composite particles containing titanium oxide particles and a resin coating the surfaces of the titanium oxide particles; A water-based ink containing water.

Citation Information

Patent Citations

  • Method for producing aqueous dispersion of white fine particles

    JP2019073595A

  • Aqueous white dispersion for inkjet ink, inkjet ink, and printed matter

    JP2021105087A